2020
DOI: 10.3389/fpls.2020.00401
|View full text |Cite
|
Sign up to set email alerts
|

Cultivar × Management Interaction to Reduce Lodging and Improve Grain Yield of Irrigated Spring Wheat: Optimising Plant Growth Regulator Use, N Application Timing, Row Spacing and Sowing Date

Abstract: Peake et al.Cultivar × Management Interaction environments and increased grain yield in response to early sowing. Further research is needed to determine the optimum management strategy for new cultivars, because farmers do not always choose the most lodging resistant cultivars for reasons of cultivar disease resistance, grain quality and seed availability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 47 publications
1
16
0
1
Order By: Relevance
“…A number of other studies have described the importance of G × E × M interactions and their contributions to crop yield productivity (Cooper et al 2001 ; Duvick et al 2004 ; Messina et al 2009 ; Hatfield and Walthall 2015 ; Beres et al 2020 ; Peake et al 2020 ; Rotili et al 2020 ; Snowdon et al 2020 ). Beyond the hybrid-by-density maize example above, a few studies have demonstrated effective improvement and utilisation of positive G × M interactions: improvement of sorghum yield for drought-prone environments in Australia (Hammer et al 2014 , 2020 ; Rodriguez et al 2018 ); improvement of wheat for drought-prone and irrigated environments in Australia (Hunt et al 2019 ); and improvement of maize hybrids for drought-prone environments of the US corn-belt by targeting selection for traits contributing to effective water use (Messina et al 2009 , 2018 ; Cooper et al 2014a , Gaffney et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of other studies have described the importance of G × E × M interactions and their contributions to crop yield productivity (Cooper et al 2001 ; Duvick et al 2004 ; Messina et al 2009 ; Hatfield and Walthall 2015 ; Beres et al 2020 ; Peake et al 2020 ; Rotili et al 2020 ; Snowdon et al 2020 ). Beyond the hybrid-by-density maize example above, a few studies have demonstrated effective improvement and utilisation of positive G × M interactions: improvement of sorghum yield for drought-prone environments in Australia (Hammer et al 2014 , 2020 ; Rodriguez et al 2018 ); improvement of wheat for drought-prone and irrigated environments in Australia (Hunt et al 2019 ); and improvement of maize hybrids for drought-prone environments of the US corn-belt by targeting selection for traits contributing to effective water use (Messina et al 2009 , 2018 ; Cooper et al 2014a , Gaffney et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This decision was supported by several other studies (Berry & Spink, 2012; Fischer & Stapper, 1987). In addition, an Australian study found severe lodging of wheat plants in early planting (Peake et al., 2020). As higher TGW strongly supported the higher grain yield, we took this trait as a positive trait in the idiotype design.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, it is believed that the application of PGRs increase grain yield (e.g., Reference [31]). Peake et al [36] reported that PGR application improved grain of most wheat varieties in well-irrigated fields, which has sufficient N supply. However, differently from the above findings, some studies reported that the PGRs application reduced the grain yield [32,37].…”
Section: Yield and Protein Contentmentioning
confidence: 99%